2020
DOI: 10.1155/2020/8275386
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Screening for Unhealthy Alcohol and Drug Use with a Brief Tablet-Based Questionnaire

Abstract: Background. Screening for unhealthy alcohol and drug use in the emergency department (ED) can be challenging due to crowding, lack of privacy, and overburdened staff. The objectives of this study were to determine the feasibility and utility of a brief tablet-based screening method in the ED and if patients would consider a face-to-face meeting with a certified alcohol and drug counselor (CADC) for more in-depth screening, brief intervention, and referral to treatment (SBIRT) helpful via this interface. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Educational programs provided by SAMHSA, the National Association of Addiction Treatment Providers (NAATP), the American Society of Addiction Management (ASAM), and multiple other organizations can help clinicians break down the biases that can lead to stigmatizing behaviors. Technologybased screening is preferable for many due to the anonymity that eases the perception of stigma associated with a disclosure of HAU (Elder et al, 2020;Hammock et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Educational programs provided by SAMHSA, the National Association of Addiction Treatment Providers (NAATP), the American Society of Addiction Management (ASAM), and multiple other organizations can help clinicians break down the biases that can lead to stigmatizing behaviors. Technologybased screening is preferable for many due to the anonymity that eases the perception of stigma associated with a disclosure of HAU (Elder et al, 2020;Hammock et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…HAU (Mojica-Perez et al, 2019). Another study in this review found that patients were more willing to complete alcohol use screening utilizing a tablet-based method as an alternative to a face-to-face encounter with a health care provider (Elder et al, 2020). The researchers administered the tablet-based questionnaire to 283 emergency department (ED) patients, and 46% of the participants were found to have unhealthy alcohol use.…”
Section: Inherent Biases Of Population Surveys and Screening Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eligible patients receive a pre-visit questionnaire that asks about pain symptoms, goals for pain management, pain treatment preferences, depression symptoms, and opioid and illicit drug use (Additional file 3 ). The questionnaire uses validated screeners to ask about current levels of pain (Pain, Enjoyment of Life, General Activity (PEG) scale), depression (PHQ-2), and drug use (drug abuse screening test (DAST-2) (ACCESS) or single-question drug use screener (UCM)) [ 13 15 ]. The I-COPE questionnaire also asks patients to identify functional goals that might be achieved through better pain management, and treatment preferences ranging from self-management to surgical intervention.…”
Section: Methodsmentioning
confidence: 99%